إِشكَالِيةُ العَقْلِ الحَدَاثِيِّ في بِناءِ المَعرفةِ الدِّينيةِ قراءة تحليلية لآراء عبدالكريم سروش (The Problem of The Modernist Mind In Constructing Religious Knowledge: An Analytical Reading of The Opinions of Abdul Karim Soroush) - عبده خالد نشوان; البقالي يونس (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
يهدف هذا البحث إلى تسليط الضوء على قراءة عبد الكريم سروش لمفهوم العقل ودوره في بناء المعرفة الدينية، حيث ذهب أن الغاية منه هو البحث والتقصي فقط وليس الوصول إلى الحق والحقيقة، وزعم أن حدود عمل العقل مطلقة لا حدود لها، وأن مخرجاته تتسم في النهاية بالنسبية إذ يصعب الوصول إلى الحقيقة وفهم الخطاب بحسب وجهة نظره، ومن أبرز نتائج هذه القراءة أن رؤية سروش هذه تؤدي إلى تقويض مفهوم العقل وإسقاط حجيته ودوره في تشكيل المعرفة الدينية ذلك لأنها جعلته في مصافِّ النسبية، وعملت على الإخلال بغرضه. الكلمات المفتاحية: العقل، الحداثة، الفكر الإسلامي، عبد الكريم سروش. Abstract This research aims to highlight Abd al-Karim Soroush’s reading of the concept of reason and its role in building religious knowledge, where the goal is to research and investigate only and not to reach the facts and truth, as he claimed that the limits of mind ability are absolute, and that its outputs are in the end relative, as it is difficult to reach the truth and understand the discourse according to his point of view. The most important result of this reading is that Soroush’s vision of the concept of reason leads to undermining this concept and dropping its authority and role in shaping religious knowledge, because it placed it in the ranks of relativism, and worked to violate its purpose. Keywords: Reason, Modernity, Islamic thought, Abdolkarim